Gene therapy for sarcoma - Frühauf, Stefan; Veldwijk, Marlon Romano; Berlinghoff, S.; Basara, N.; Baum, C.; Flasshove, M.; Hegewisch-Becker, S.; Kröger, N.; Licht, T.; Moritz, T.; Hengge, U. R.; Zeller, W. Jens; et al. (Cells tissues organs, 2002)
Soft tissue sarcomas are mesenchymal tumors which respond poorly to systemic therapy. Recent studies suggest a higher response rate with an increased doxorubicin dosage. However, this was parallel with a profound hematotoxicity in 75% of patients. Transfer of the human multidrug resistance 1 (MDR1) gene to normal hematopoietic stem cells and transplantation may significantly reduce the hematotoxicity of anthracyclin-based chemotherapy.